Dorsal root ganglion neurons innervating pelvic organs in the mouse express tyrosine hydroxylase - Brumovsky, Pablo R. (2012)
Previous studies in rat and mouse documented that a subpopulation of dorsal root ganglion (DRG) neurons innervating non-visceral tissues express tyrosine hydroxylase (TH). Here we studied whether or not mouse DRG neurons retrogradely traced with Fast Blue (FB) from colorectal or urinary bladder also express immunohistochemically detectable TH. The lumbar sympathetic chain (LSC) and major pelvic ganglion (MPG) were included in the analysis. Previously characterized antibodies against TH, norepinephrine transporter type 1 (NET-1) and calcitonin gene-related peptide (CGRP) were used. On average, 14% of colorectal and 17 % of urinary bladder DRG neurons expressed TH and spanned virtually all neuronal sizes, although more often in the medium-sized to small ranges. Also, they were more abundant in lumbosacral than thoracolumbar DRGs, and often coexpressed CGRP. We also detected several TH-immunoreactive (IR) colorectal and urinary bladder neurons in the LSC and the MPG, more frequently in the former. No NET-1-IR neurons were detected in DRGs, whereas the majority of FB-labeled, TH-IR neurons in the LSC and MPG coexpressed this marker (as did most other THIR neurons not labeled from the target organs). TH-IR nerve fibers were detected in all layers of the colorectum and the urinary bladder, with some also reaching the basal mucosal cells. Most TH-IR fibers in these organs lacked CGRP. Taken together, we show: 1) that a previously undescribed population of colorectal and urinary bladder DRG neurons expresses TH, often CGRP but not NET-1, suggesting absence of a noradrenergic phenotype; and 2) that TH-IR axons/terminals in colon or urinary bladder, naturally expected to derive from autonomic sources, could also originate from sensory neurons.